Konsep Balance Dalam Ayat Etos Kerja: Analisis QS. Al-Syarh: 7, QS. Al-Qaṣaṣ: 77 dan QS. Al-Jumu’ah: 10 Perspektif Tafsir Maqashidi - Avif Alfiyah; Wilujeng Luthfiyah; Nidaul Ishlaha (QOF, 2022)
This research presents a new reading on the work ethics verses through the principle of maqasid. This is intended to seek the moderation value bertween religionas the sacred and the profane often creates a misperception on superiority of worship as a whole religion. The assumption worship in totally is without being preoccupied with the profane  is in fact not in line with the QS. Sharh{: 7-8, al-Qashash: 77 and al-Jumu’ah 10 as a group of the Qur’an verves which is the focus of this research. Through this, the views of the Qur’an wil be presented regarding the concept of moderation berween the demand of worship and work in a balanced and proportional manner. This uses maqasid approach to discover the values of maqa>s{id al-Qur’a>n dan maqashid as-syari’ah. The result of this research indicate from a group verses have been mentioned there are balues of balance between worship and work. It is also mean that the interest of the hereafter can not be separated from worldly intereset, all of which mus be carried out in balanced manner according to their respective portions.